RISK FACTORS FOR RENAL CELL CARCINOMA - D. G. Zaridze; A. F. Mukeria; O. V. Shangina (Сибирский онкологический журнал, 2018)
Smoking, overweight, obesity, hypertension, occupational exposures to pesticides, specifically to trichloroethylene are considered causal risk factors for sporadic i.e. non-hereditary renal cell cancer (RCC). Some of these factors not only increase the risk of RCC but also affect the survival of patients. For example, in patients with RCC who continue smoking, the risk of dying from other causes is twice as high as in patient who quit smoking. The risk of second cancer is 5 times higher in patients who continue smoking 20 or more cigarettes per day than in non-smokers. The low penetrance polymorphism is an important factor in etiology of sporadic RCC, which contrary to high penetrance mutations is a common event. However, the risk associated with this type of inheritance is quite low. The majority of sporadic RCC have polygenic etiology. They develop as a result of combined effect of large number of low penetrance genetic susceptibility genes (genetic polymorphism). Environmental factors play a decisive role in causation of sporadic RCC. The interplay of exposures to environmental risk factors and genetic susceptibility of exposed individuals is believed to influence the risk of developing sporadic RCC. The studies in molecular epidemiology based on candidate gene approach have shown that polymorphisms of certain genes, for example glutathione-S-transferase family genes, are associated with RCC. The genome wide association studies identified about twenty loci with single nucleotide polymorphism (SNPs) affecting the risk of RCC. However the risk loci so far identified for RCC account for only about 10 % of the familial risk of RCC. The power of largest studies which include many thousands of observations allow to detect 80 % of the major common loci (with minor allele frequency – MAF>0.2) conferring risk ≥1.2. However, for detecting alleles with smaller effects and/or MAF<0.1, more studies with larger sample size are needed. By implication, variants with such profiles probably represent a much larger class of susceptibility loci for RCC and hence a large number of variants remain to be discovered. Future investigation of the genes targeted by the risk SNPs is likely to yield increased insight into biology of RCC and will lead to new approaches for prevention, early detection and treatment.